Saltwater intrusion vulnerability in a dynamic coastal plain: interplay among subsidence and ecological changes in the Volturno River plain (southern Italy) - Lucia Rita Pacifico; Annarita Casaburi; Raffaele D'Adamo; Adele Fabbrocini; Laura Giordano; Luciana Ferraro; Antonio Mercadante; Flavia Molisso; Fabio Matano (Quaternary International, 2026)

Monte San Nicola (Sicily): Gelasian GSSP and base Quaternary/Pleistocene - L. Capraro; S. Bonomo; A. Incarbona; F.J. Hilgen; E. Zanola; A. Di Stefano; F. Dela Pierre; S. Ferraro; P. Ferretti; E. Fornaciari; S. Galeotti; P. Macrì; et al. (Quaternary Science Reviews, 2026)

Evaluation of coal combustion residuals in cement systems - Ashish D. Patel; Jordan K. Magnuson; Timothy G. Townsend; Christopher C. Ferraro (Journal of Hazardous Materials, 2026)

Structural constraints and environmental convergence: multilevel governance and $${CO}_{2}$$reduction in Italian provinces - Massimiliano Agovino; Maria D’Avino; Aniello Ferraro; Katia Marchesano (International Environmental Agreements: Politics, Law and Economics, 2026)

Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)

Environmental analysis of a ten-year pilot project using municipal solid waste incinerator bottom ash as road base: a case study - Jordan K. Magnuson; Kate D. Weiksnar; Steven J. Laux; Justin G. Roessler; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2026)

Food limitation erodes the thermal tolerance of larvae in an ecologically influential marine herbivore - Maya J. Munstermann; Sam E. Karelitz; Rachele Ferraro; Laura Rogers‐Bennett; Rachel D. Simons; Daniel K. Okamoto (Ecology, 2026)
Biologists often use organismal thermal tolerance to help explain or forecast responses of populations to climate change. Yet many studies quantify thermal tolerance under isolated laboratory conditions despite extreme events, such as heatwaves, often coinciding with other stressors such as nutrient or food limitation. These oversights may be consequential as recent theory suggests thermal tolerance itself can be fundamentally altered by food limitation. Here, we experimentally test how food limitation (500–10,000 cells mL −1 ) affects long‐term survival, development, and growth across a present‐day range of temperatures (10–20°C) in the most sensitive life stages of an important marine herbivore, purple sea urchins ( Strongylocentrotus purpuratus ). We show food limitation substantially erodes thermal tolerance in terms of survival, but when provided ample food, larvae exhibited robust survival across temperatures currently experienced by larvae in nature. Reductions in food however lowered optimal survival temperatures and shifted survival thresholds to those conditions observed during recent marine heatwaves. These results are consistent with the “metabolic meltdown” hypothesis—shifting optima and upper limits to cooler temperatures—and illustrate how present‐day warming coupled with lower productivity may lead to substantial, unexpected declines in larval survival and recruitment. In contrast to survival, developmental rates and time to metamorphic competency, which ranged from 21 to 61 days, were driven largely by temperature with little impact of food concentration. Our findings relate to historical observations of declines in larval supply at the southern edge of the species range. Overall, these results have broad‐reaching implications beyond sea urchin populations as sea urchin herbivory is known to control productivity of kelp forest communities. We provide evidence of how laboratory derived thermal reaction norms can be coupled with ecologically relevant food concentrations to inform unexpected vital rate declines of sensitive life stages in a changing climate.

Detection of Dengue virus RNA in Wastewater during a Local Epidemic in Central Italy (August–October 2024) - P. Mancini; C. Veneri; G. Bonanno Ferraro; A. Franco; M. Iaconelli; D. Brandtner; L. Lucentini; G. Venturi; E. Mancuso; G. Marsili; M. Del Manso; C. Sacco; et al. (Food and Environmental Virology, 2025)

Evaluation of alkali-silica reactivity behavior and mitigation in waste-to-energy bottom ash for sustainable aggregate use in concrete - Kate D. Weiksnar; Jordan K. Magnuson; Ashish D. Patel; Robbie Posada; Christopher C. Ferraro; Timothy G. Townsend (Waste Management, 2025)

Sedimentological and biostratigraphic reconstruction of the Early Pleistocene San Giuliano Lake section (Matera, Southern Italy) - F.O. Amore; C. Argenio; C. Faranda; L. Ferraro; E. Gliozzi; D. Magri; F. Michelangeli; B. Russo; J. Siciliano; M. Vallefuoco; A. Mauro; A. Meo; et al. (Quaternary International, 2025)

A review of the suitability and performance of phosphogypsum as a material for road base and subbase construction - Malik A. DeWindt; Kate D. Weiksnar; Steven J. Laux; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2025)

Climate change and occupational health and safety. Risk of injuries, productivity loss and the co-benefits perspective - A. Marinaccio; C. Gariazzo; L. Taiano; M. Bonafede; D. Martini; S. D'Amario; F. de’Donato; M. Morabito; Filippo Ariani; Alessandra Binazzi; Andrea Bogi; Michela Bonafede; et al. (Environmental Research, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Global quantification and distribution of antibiotic resistance genes in oceans and seas: Anthropogenic impacts and regional variability - G. Bonanno Ferraro; D. Brandtner; A. Franco; M. Iaconelli; P. Mancini; C. Veneri; R. Briancesco; A.M. Coccia; E. Suffredini; A. Muratore; F. Ferrara; L. Lucentini; et al. (Science of The Total Environment, 2024)

Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Impacts of advanced metals recovery on municipal solid waste incineration bottom ash: aggregate characteristics and performance in portland limestone cement concrete - Kate D. Weiksnar; Ethan J. Marks; Margaret J. Deaderick; Isabella Meija-Ruiz; Christopher C. Ferraro; Timothy G. Townsend (Waste Management, 2024)

Individuals in focus: Individuals as the ecological and ethical center of human-wildlife conflict - Kaggie D. Orrick; Kristy M. Ferraro; Nathalie R. Sommer (Biological Conservation, 2024)

Tyndallized bacteria prime bronchial epithelial cells to mount an effective innate immune response against infections - Serena Di Vincenzo; Caterina Di Sano; Claudia D’Anna; Maria Ferraro; Velia Malizia; Andreina Bruno; Marta Cristaldi; Chiara Cipollina; Valentina Lazzara; Paola Pinto; Stefania La Grutta; Elisabetta Pace (Human Cell, 2024)
Airway epithelium represents a physical barrier against toxic substances and pathogens but also presents pattern recognition receptors on the epithelial cells that detect pathogens leading to molecule release and sending signals that activate both the innate and adaptive immune responses. Thus, impaired airway epithelial function and poor integrity may increase the recurrence of infections. Probiotic use in respiratory diseases as adjuvant of traditional therapy is increasingly widespread. There is growing interest in the use of non-viable heat-killed bacteria, such as tyndallized bacteria (TB), due to safety concerns and to their immunomodulatory properties. This study explores in vitro the effects of a TB blend on the immune activation of airway epithelium. 16HBE bronchial epithelial cells were exposed to different concentrations of TB. Cell viability, TB internalization, TLR2 expression, IL-6, IL-8 and TGF-βl expression/release, E-cadherin expression and wound healing were assessed. We found that TB were tolerated, internalized, increased TLR2, E-cadherin expression, IL-6 release and wound healing but decreased both IL-8 and TGF-βl release. In conclusion, TB activate TLR2 pathway without inducing a relevant pro-inflammatory response and improve barrier function, leading to the concept that TB preserve epithelial homeostasis and could be used as strategy to prevent and to manage respiratory infection, exacerbations included.

Detection and full genomic sequencing of rare hepatitis E virus genotype 4d in Italian wastewater, undetected by clinical surveillance - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; C. Del Giudice; A.R. Ciccaglione; R. Bruni; M. Equestre; C. Marcantonio; E. Suffredini; G. La Rosa (Science of The Total Environment, 2024)

Processing municipal solid waste incineration bottom ash for integration into cement product manufacture - Jordan K. Magnuson; Kate D. Weiksnar; Ashish D. Patel; Kyle A. Clavier; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2023)

Applying behavioral science to agriculture, food, and agri-environmental policymaking - Pallavi Shukla; Kent D. Messer; Paul J. Ferraro (Food Policy, 2023)

Informational nudges in conservation auctions: A field experiment with U.S. farmers - Steven Wallander; Laura A. Paul; Paul J. Ferraro; Kent D. Messer; Richard Iovanna (Food Policy, 2023)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

A microfluidic device for extracellular vesicle purification: an in-vitro study on mammary gland tumours - V. Moccia; A. Meggiolaro; P. Brun; A. Sammarco; D. Ferraro; V. Zappulli (Journal of Comparative Pathology, 2023)

What killed the rarest snake in North America? - Kevin M. Enge; Jaimi A. Gray; Coleman M. Sheehy; Trudy Ferraro; Drew M. Martin; Jonathan D. Mays (Ecology, 2023)

A State-of-the-Art Scoping Review on SARS-CoV-2 in Sewage Focusing on the Potential of Wastewater Surveillance for the Monitoring of the COVID-19 Pandemic - G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; E. Suffredini; L. Bonadonna; L. Lucentini; A. Bowo-Ngandji; C. Kengne-Nde; D. S. Mbaga; G. Mahamat; H. R. Tazokong; et al. (Food and Environmental Virology, 2022)

Hepatitis E Virus in Water Environments: A Systematic Review and Meta-analysis - G. R. Takuissu; S. Kenmoe; L. Ndip; J. T. Ebogo-Belobo; C. Kengne-Ndé; D. S. Mbaga; A. Bowo-Ngandji; M. G. Oyono; R. Kenfack-Momo; S. Tchatchouang; J. Kenfack-Zanguim; R. Lontuo Fogang; et al. (Food and Environmental Virology, 2022)
Hepatitis E virus (HEV) is responsible for acute hepatitis in humans, through foodborne, zoonotic, and waterborne transmission routes. This study aimed to assess the prevalence of HEV in water matrices. Six categories were defined: untreated and treated wastewater, surface water (river, lake, and seawater), drinking water, groundwater, and other water environments (irrigation water, grey water, reservoir water, flood water, and effluent of pig slaughterhouse). We searched PubMed, Web of Science, Global Index Medicus, and Excerpta Medica Database. Study selection and data extraction were performed by at least two independent investigators. Heterogeneity ( I 2 ) was assessed using the χ 2 test on the Cochran Q statistic and H parameter. Sources of heterogeneity were explored by subgroup analysis. This study is registered with PROSPERO, number CRD42021289116. We included 87 prevalence studies from 58 papers, 66.4% of which performed in Europe. The overall prevalence of HEV in water was 9.8% (95% CI 6.4–13.7). The prevalence was higher in untreated wastewater (15.1%) and lower in treated wastewater (3.8%) and in drinking water (4.7%). In surface water, prevalence was 7.4%, and in groundwater, the percentage of positive samples, from only one study available, was 8.3%. Overall, only 36.8% of the studies reported the genotype of HEV, with genotype 3 (HEV-3) prevalent (168 samples), followed by HEV-1 (148 sample), and HEV-4 (2 samples). High-income countries were the most represented with 59/87 studies (67.8%), while only 3/87 (3.5%) of the studies were performed in low-income countries. The overall prevalence obtained of this study was generally higher in industrialized countries. Risk of bias was low in 14.9% of the studies and moderate in 85.1%. The results of this review showed the occurrence of HEV in different waters environments also in industrialized countries with sanitation and safe water supplies. While HEV transmission to humans through water has been widely demonstrated in developing countries, it is an issue still pending in industrialized countries. Better knowledge on the source of pollution, occurrence, survival in water, and removal by water treatment is needed to unravel this transmission path. Graphical Abstract

Effectiveness of a Team-Based Learning exercise in the learning outcomes of a medical pharmacology course: insight from struggling students - Gonzalo A. Carrasco; Kathryn C. Behling; Matthew Gentile; Bradford D. Fischer; Thomas N. Ferraro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

The search for blue transitions in aquaculture‐dominant countries - Richard S. Cottrell; Danielle M. Ferraro; Gordon D. Blasco; Benjamin S. Halpern; Halley E. Froehlich (Fish and Fisheries, 2021)
The capacity for aquaculture to provide an alternative source of fish and seafood to capture fisheries was once promoted as a tool to reduce demand for wild fish and thus tackle overfishing. To date, there is little evidence to suggest that aquaculture growth has successfully reduced fishing effort on wild populations. Recent theory on “blue transitions” suggests that displacement may only occur as aquaculture production surpasses that of capture operations. Yet, there has been no systematic attempt to understand whether aquaculture‐driven fisheries displacement has occurred in countries where aquaculture is now the dominant production form. We investigate the role of aquaculture on fisheries landings in these “aquaculture‐dominant” countries using national‐level production, trade, consumption and socioeconomic data from 1980 to 2017. Importantly, we find that aquaculture growth is associated with fisheries decline in aquaculture‐dominant countries, but the marginal effects of aquaculture have a far weaker influence on wild‐caught landings than other promoting factors, such as fish consumption and trade. Further, our qualitative analysis of the state of wild fisheries in aquaculture‐dominant nations suggests that overexploitation continues to be pervasive and that any minimal displacement effects from aquaculture are unlikely to have offset the environmental impacts imposed by the growing sector. The rise of aquaculture as an alternative production form can provide valuable insights for growing industries developing sustainable new foods. Unless coupled with effective food consumption policy, such products may simply add to rather than displace the environmental impacts of human food production.

The long and narrow path for novel cell‐based seafood to reduce fishing pressure for marine ecosystem recovery - Benjamin S. Halpern; Jason Maier; Heather J. Lahr; Gordon Blasco; Christopher Costello; Richard S. Cottrell; Olivier Deschenes; Danielle M. Ferraro; Halley E. Froehlich; Gavin G. McDonald; Katherine D. Millage; Michael J. Weir (Fish and Fisheries, 2021)
Cell‐based seafood is an emerging novel food, with many start‐up companies aspiring for ocean conservation benefits through expanded market share that displaces wild‐caught seafood. However, the ability for cell‐based seafood to achieve this conservation outcome is often oversimplified and will rely on an extensive, and we find somewhat tenuous, chain of events. Here, we outline the technological, behavioural, market and ecological changes that must occur along this pathway, and conclude that fisheries recoveries and collateral ocean benefits are unlikely to result from cell‐based seafood technology. In particular, we detail nine necessary steps and argue that failure at any one step could hinder or even eliminate cell‐based seafood's conservation effects. We additionally draw comparisons to aquaculture and share broader lessons for other demand‐driven product interventions.

Substantial Gaps in the Current Fisheries Data Landscape - Gordon D. Blasco; Danielle M. Ferraro; Richard S. Cottrell; Benjamin S. Halpern; Halley E. Froehlich (Frontiers in Marine Science, 2020)
Effective management of aquatic resources, wild and farmed, has implications for the livelihoods of dependent communities, food security, and ecosystem health. Good management requires information on the status of harvested species, yet many gaps remain in our understanding of these species and systems, in particular the lack of taxonomic resolution of harvested species. To assess these gaps we compared the occurrence of landed species (freshwater and marine) from the United Nations Food and Agriculture Organization (FAO) global fisheries production database to those in the International Union for Conservation of Nature (IUCN) Red List and the RAM Legacy Stock Assessment Database, some of the largest and most comprehensive global datasets of consumed aquatic species. We also quantified the level of resolution and trends in taxonomic reporting for all landed taxa in the FAO database. Of the 1,695 consumed aquatic species or groups in the FAO database considered in this analysis, a large portion (35%) are missing from both of the other two global datasets, either IUCN or RAM, used to monitor, manage, and protect aquatic resources. Only a small number of all fished taxa reported in FAO data (150 out of 1,695; 9%) have both a stock assessment in RAM and a conservation assessment in IUCN. Furthermore, 40% of wild caught landings are not reported to the species level, limiting our ability to effectively account for the environmental impacts of wild harvest. Landings of invertebrates (44%) and landings in Asia (>75%) accounted for the majority of harvest without species specific information in 2018. Assessing the overlap of species which are both farmed and fished to broadly map possible interactions – which can help or hinder wild populations - we found 296 species, accounting for 12% of total wild landings globally, and 103 countries and territories that have overlap in the species caught in the wild and produced through aquaculture. In all, our work highlights that while fisheries management is improving in many areas there remain key gaps in data resolution that are critical for fisheries assessments and conservation of aquatic systems into the future.

Trend analysis of significant wave height and energy period in southern Italy - T. Caloiero; F. Aristodemo; D. Algieri Ferraro (Theoretical and Applied Climatology, 2019)

Velocity scales in steady-nonuniform turbulent flows with low relative submergence - D. Ferraro; S. Servidio; R. Gaudio (Environmental Fluid Mechanics, 2019)

Historical maps and satellite images as tools for shoreline variations and territorial changes assessment: the case study of Volturno Coastal Plain (Southern Italy) - I. Alberico; G. Cavuoto; V. Di Fiore; M. Punzo; D. Tarallo; N. Pelosi; L. Ferraro; E. Marsella (Journal of Coastal Conservation, 2018)

Winter precipitation characteristics in western US related to atmospheric river landfalls: observations and model evaluations - J. Kim; B. Guan; D. E. Waliser; R. D. Ferraro; J. L. Case; T. Iguchi; E. Kemp; W. Putman; W. Wang; D. Wu; B. Tian (Climate Dynamics, 2018)

The neural correlates of lexical processing in disorders of consciousness - Anna Nigri; Eleonora Catricalà; Stefania Ferraro; Maria Grazia Bruzzone; Ludovico D’Incerti; Davide Sattin; Davide Rossi Sebastiano; Silvana Franceschetti; Giorgio Marotta; Riccardo Benti; Matilde Leonardi; Stefano F. Cappa (Brain Imaging and Behavior, 2017)

Investigation of different ethylenediamine-N,N′-disuccinic acid-enhanced washing configurations for remediation of a Cu-contaminated soil: process kinetics and efficiency comparison between single-stage and multi-stage configurations - Alberto Ferraro; Massimiliano Fabbricino; Eric D. van Hullebusch; Giovanni Esposito (Environmental Science and Pollution Research, 2017)

Calibration and Validation of a Two-Step Kinetic Mathematical Model for Predicting Cu Extraction Efficiency in an EDDS-Enhanced Soil Washing - Alberto Ferraro; Massimiliano Fabbricino; Eric D. van Hullebusch; Giovanni Esposito (Water, Air, & Soil Pollution, 2016)

Effect of soil/contamination characteristics and process operational conditions on aminopolycarboxylates enhanced soil washing for heavy metals removal: a review - Alberto Ferraro; Massimiliano Fabbricino; Eric D. van Hullebusch; Giovanni Esposito; Francesco Pirozzi (Reviews in Environmental Science and Bio/Technology, 2016)

Multi-center evaluation of the VITEK® MS system for mass spectrometric identification of non-Enterobacteriaceae Gram-negative bacilli - R. Manji; M. Bythrow; J. A. Branda; C.-A. D. Burnham; M. J. Ferraro; O. B. Garner; R. Jennemann; M. A. Lewinski; A. B. Mochon; G. W. Procop; S. S. Richter; J. A. Rychert; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Pulmonary Inflammation and Cell Death in Mice After Acute Exposure to Air Particulate Matter From an Industrial Region of Buenos Aires - F. Astort; M. Sittner; S. A. Ferraro; N. S. Orona; G. A. Maglione; A. De la Hoz; D. R. Tasat (Archives of Environmental Contamination and Toxicology, 2013)

Recurrent Varicella following Steroids and Fingolimod in a Multiple Sclerosis Patient - D. Ferraro; S. De Biasi; F. Vitetta; A. M. Simone; L. Federzoni; V. Borghi; A. Cossarizza; P. F. Nichelli; P. Sola (Journal of Neuroimmune Pharmacology, 2013)

Identification of Enterobacteriaceae by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry using the VITEK MS system - S. S. Richter; L. Sercia; J. A. Branda; C.-A. D. Burnham; M. Bythrow; M. J. Ferraro; O. B. Garner; C. C. Ginocchio; R. Jennemann; M. A. Lewinski; R. Manji; A. B. Mochon; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Current views on EDDS use for ex situ washing of potentially toxic metal contaminated soils - M. Fabbricino; A. Ferraro; G. Del Giudice; L. d’Antonio (Reviews in Environmental Science and Bio/Technology, 2013)

Evolution of the Sele River coastal plain (southern Italy) during the Late Quaternary by inland and offshore stratigraphical analyses - Pietro P. C. Aucelli; Vincenzo Amato; Francesca Budillon; Maria Rosaria Senatore; Sabrina Amodio; Carmine D’Amico; Simone Da Prato; Luciana Ferraro; Gerardo Pappone; Elda Russo Ermolli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2012)

Holocene environmental evolution of the costal sector in front of the Poseidonia-Paestum archaeological area (Sele plain, southern Italy) - Vincenzo Amato; Pietro Patrizio Ciro Aucelli; Bruno D’Argenio; Simone Da Prato; Luciana Ferraro; Gerardo Pappone; Paola Petrosino; Carmen Maria Rosskopf; Elda Russo Ermolli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2012)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Long term monitoring of oil spills in European seas - G. Ferraro; S. Meyer‐Roux; O. Muellenhoff; M. Pavliha; J. Svetak; D. Tarchi; K. Topouzelis (International Journal of Remote Sensing, 2009)

Regioselective Disulfide Solid Phase Synthesis, Chemical Characterization and In Vitro Receptor Binding Activity of Equine Relaxin - Mohammed Akhter Hossain; Feng Lin; Soude Zhang; Tania Ferraro; Ross A. Bathgate; Geoffrey W. Tregear; John D. Wade (International Journal of Peptide Research and Therapeutics, 2006)

Plasticity of repetitive DNA in response to metal stress in Bryophytes - P. Bassi; A. Basile; M. Ferraro; M. Masi; D. Migliaccio; G. Morelli; E. Napolitano (Plant Biosystems, 2006)

Distribution of VP7 serotypes and VP4 genotypes among rotavirus strains recovered from Italian children with diarrhea - S. Arista; E. Vizzi; D. Ferraro; A. Cascio; R. Di Stefano (Archives of Virology, 1997)

Almost equivalence of combinatorial and distance processes for discrimination in multielement images - M. Ferraro; D. H. Foster (Biological Cybernetics, 1991)

Le pollinosi da oleacee. Indagine aerobiologica nell'atmosfera della città di Palermo - I. Cricchio; M. Zambito; A. Ferraro; D. Minutella; S. Corrao; E. Fileccia; G. Passalacqua (Aerobiologia, 1987)